2019
DOI: 10.1371/journal.pone.0209843
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and biomolecular effects induced by a static magnetic field in Saccharomyces cerevisiae: Evidence for oxidative stress

Abstract: Exposure to static magnetic fields (SMF) can cause changes in microorganism metabolism altering key subcellular functions. The purpose of this study was to investigate whether an applied SMF could induce biological effects on growth of Saccharomyces cerevisiae, and then to probe biochemical and bio-molecular responses. We found a decrease in growth and viability under SMF (250mT) after 6h with a significant decrease in colony forming units followed by an increase between 6 h and 9 h. Moreover, measurements of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…MFs can be divided into two categories: the static magnetic field (SMF) generated by a permanent magnet or direct current passing through a metal coil, whose north and south poles are typically unchanged in the same experiment [ 9 ]; and the alternative magnetic field (AMF) generated by an alternating current through the metal coil, whose north and south poles change with the frequency of the alternating current [ 14 ]. The effects of various types of MFs on the growth and metabolism of microorganisms have mainly involved bacteria [ 15 , 16 ] and yeasts [ 17 , 18 ]. For example, exposure of Komagataeibacter xylinus ATCC 53524 to 50 Hz AMF resulted in an increase in bacterial cellulose yield and a drop in fructose consumption [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…MFs can be divided into two categories: the static magnetic field (SMF) generated by a permanent magnet or direct current passing through a metal coil, whose north and south poles are typically unchanged in the same experiment [ 9 ]; and the alternative magnetic field (AMF) generated by an alternating current through the metal coil, whose north and south poles change with the frequency of the alternating current [ 14 ]. The effects of various types of MFs on the growth and metabolism of microorganisms have mainly involved bacteria [ 15 , 16 ] and yeasts [ 17 , 18 ]. For example, exposure of Komagataeibacter xylinus ATCC 53524 to 50 Hz AMF resulted in an increase in bacterial cellulose yield and a drop in fructose consumption [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Biosynthesized AgNPs formed under both conditions displayed pronounced antimicrobial and antibiofilm activities with two model pathogenic microorganisms. We hypothesize that yeast cells stressed by SMF secrete reductases and/or reducing agents in response to oxidative stress 17 . These likely promote more efficient reduction of silver forming AgNPs.…”
Section: Resultsmentioning
confidence: 99%
“…Investigation of the effect of SMF on cultured mammalian and microbial cells also indicated an increase in oxidative stress 16 . A recent study demonstrated that baker’s yeast, Saccharomyces cerevisiae , experiences oxidative stress and profound reduction in growth rate in the presence of weak SMF 17 . Here, we explore a novel green chemistry approach to biosynthesis of AgNPs using cell-free supernatants of S. cerevisiae cultures grown in the presence and absence of SMF.…”
Section: Introductionmentioning
confidence: 99%
“…The use of various types of force fields (e.g., magnetic, electrical, ultrasound) is a promising alternative to traditional methods of intensification of biomass production. It was already shown that static magnetic fields (SMF) display a high potential for stimulating the growth of certain microbial species and for increasing the level of enzyme production [20][21][22]. In turn, recent reports of our team and other researchers indicate the applicability of the rotating MF (RMF) for various biotechnological processes, including BC biogenesis [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 91%